Task-Level Energy Efficiency Evaluation Method Based on Aero-Engine Thrust-Specific Fuel Consumption with Application to Environment Control System - Haodong Liu; Sujun Dong; Hongsheng Jiang; Yuanye Zhou; Yongji Liu; Jianjun Wu (Machines, 2022)
There has recently been a considerable and dramatic change in the system design of some future aircraft. The use of electrical energy has led to a demand for rapid technology development in the environment control system (ECS). Extracting energy from the aero-engine in the form of compressed air and electric power to drive the ECS directly affects aero-engine fuel economy. There is an urgent demand for a task-level energy efficiency evaluation method to guide energy and heat sink scheduling. This paper takes the F22 Raptor fighter jet as the research object and analyzes the influence of bleed air and electric power on the thrust and thrust-specific fuel consumption (TSFC) based on the exergy analysis method. First, a two-step TSFC surrogate model is constructed, and a task-level energy efficiency evaluation method is proposed. The error of the TSFC surrogate model is less than 5%, which means the accuracy of the model is sufficient to meet the needs of engineering. Then, the task-level energy efficiency evaluation results show that the vapor cycle has significant fuel economy when the cooling capacity is large, while the air cycle has certain advantages with a small cooling capacity. The method of TSFC surrogate model reduces computational complexity of evaluation with enough accuracy, which can provide a reference for selecting ECS type and guide the optimization of the cooling capacity distribution of the air cycle and vapor cycle.